Na constelação da excitação: reflexões sobre a formação docente em educação física a partir do diálogo com a teoria crítica da sociedade de Christoph Türcke - Souza, Darlei Francisco de (2018)
The current dissertation constitutes of a paper of theoretical nature that aimed at studying a part of the German philosopher Christoph Türcke’s work, currently considered one of the main representatives of the theory called Critical Theory of Society. The aim of this paper constituted of pointing out the possible contributions to the field of forces of the Physical Education teacher graduation resulting from the dialogue with the author’s theoretical formulations. The need to carry out such discussion resides in the fact that Türcke’s philosophical works present us some robust critical reading on the contemporary capitalistic society. Such reading is fundamental for us to understand and face the most recent challenges related to the problematic of human formation, mainly in the contexts penetrated by high technology, in which one can verify a ubiquity of sensorial stimuli that reshape the set of relationships of our society, so much so that it is possible to affirm with certainty that we live in a hyperactivity culture, or as Türcke (2010b; 2016a) puts it, “attention deficit disorder culture”. Thus, we ask ourselves in this dissertation: in what ways does the dialogue with Christoph Türcke’s works contribute to thinking the Physical Education teacher graduation facing the challenges posed by the culture called hyperactivity culture or attention deficit disorder culture? Guided by this question, we carried out a thorough examination of the conceptual constellation built by Türcke in his papers Philosophy of dreams (2010b), Hyperactive: down with the attention deficit disorder culture (2016a), as well as interviews published in Portuguese. Besides that, we make use of some elements which were developed by the author in Excited Society: philosophy of sensation (2010a). We also sought to dialogue with the Brazilian interpreters that study these works in order to better understand the author’s thinking so that, by doing so, we can attempt at a critical reflection about the Physical Education teacher graduation in the context of hyperactivity culture or attention deficit disorder culture. This way, we divided the paper into four chapters. In the first of them, we sought to introduce the area of Physical Education, with special dedication to the way in which the subject of teacher graduation is structured in the field, emphasizing the main challenges pointed out in literature and arguing how the body overwhelmed by sensorial stimuli has constituted a challenge for the graduation of teachers in the area. In the second chapter, we sought to trace Türcke’s biographic and formative trajectory, attempting to evidence the theoretical influences that constitute the basis of his thinking, as well as the location of points of advancement which his theory can provide for the reflection about the formative phenomenon of the contemporary society. In the third chapter, we dedicated to the analysis and discussion of the theoretical formulations that are present in the analyzed works in order to — in the fourth chapter — show the contribution of this dialogue to the Physical Education teacher graduation, above all, to what two points concern: i) the teachers’ own process of graduation; ii) the challenges that are expressed in their daily work in schools resulting from the attention deficit disorder culture.